Independent Thinking in Graphic Education Application of Reinforced Interactive Methods - Yakubova Barno Bakhtiyarovna (Genius Journals, 2022)
This article describes approaches to interacting methodos of teaching graphics discipline to manage ring independently work of students. It is written about the ability of a modern teacher as a manager-coordinator, tutor, guide, to guide the correct formation of students' independent thinking ability, to consistently strengthen skills, to have the ability to rationally organize and effectively manage students' independent education.
Keywords: descriptive geometry; influence self-contained; methodical; motivational